MAC Protocols for Energy Harvesting Wireless Sensor Networks: Survey. Issue 4 (1st August 2015) - Kosunalp, Selahattin
Abstract : Energy harvesting (EH) technology in the field of wireless sensor networks (WSNs) is gaining increasing popularity through removing the burden of having to replace/recharge depleted energy sources by energy harvester devices. EH provides an alternative source of energy from the surrounding environment; therefore, by exploiting the EH process, WSNs can achieve a perpetual lifetime. In view of this, emphasis is being placed on the design of new medium access control (MAC) protocols that aim to maximize the lifetime of WSNs by using the maximum possible amount of harvested energy instead of saving any residual energy, given that the rate of energy harvested is greater than that which is consumed. Various MAC protocols with the objective of exploiting ambient energy have been proposed for energy‐harvesting WSNs (EH‐WSNs). In this paper, first, the fundamental properties of EH‐WSN architecture are outlined. Then, several MAC protocols proposed for EH‐WSNs are presented, describing their operating principles and underlying features. To give an insight into future research directions, open research issues (key ideas) with respect to design trade‐offs are discussed at the end of this paper.